Engagement with Special Olympics by the general public in 17 countries world-wide. Issue 9 (2nd September 2022) - McConkey, Roy; Slater, Paul; Dubois, Lindsay; Shellard, Amy; Smith, Ashlyn
Abstract: Over five million athletes with intellectual disability (ID) currently participate in Special Olympics (SO) worldwide with the broader aim of promoting their inclusion in society. The public's knowledge of SO was determined in 17 selected countries globally and the characteristics of those most actively involved identified. Online, self-completion surveys were completed by 36, 508 nationally representative respondents. Around 1 in 7 people globally reported an active involvement with SO and a further third were aware of it through the media. Engagement was greater among respondents who had experience in volunteering, playing sports and frequent personal contact with people with ID. Only one quarter of respondents correctly distinguished SO from Paralympics and the Olympic Games. There is scope to make the public more aware of, and better informed about SO. Further research examines the relationships between engagement with SO and public attitudes towards the inclusion of persons with ID in wider society.